PENERAPAN METODE PEMODELAN UNTUK MENINGKATKAN KEMAMPUAN MEMBACA NASKAH DRAMA ANAK-ANAK PADA SISWA KELAS IV MIN 41 PIDIE - Nanda Saputra (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
The aim is to find out the increase in the ability to read children's drama scripts in class IV MIN 41 Pidie by using a modeling model. The approach used in this study is a qualitative approach to the type of Classroom Action Research (CAR). Data taken from test results, observations, and interview results. The data source is students in class IV MIN 41 Pidie totaling 38 students with various levels of ability. The results showed that the modeling method could improve students' ability to read children's drama scripts. This is evidenced by the increasing number of students who have finished learning from 39% at the pre-action test or before learning takes place. Then it increased to 76% in the first cycle, and increased again to 89% in the second cycle. The use of modeling methods can also increase the activity of teachers and grade IV students at MIN 41 Pidie when learning to read children's drama scripts. This is proven by an increase in the percentage of teacher activity in the first cycle 81% to 91% in the second cycle. Student activities in the first cycle that is 83% to 93% in the second cycle.